2020
DOI: 10.1080/25741292.2020.1841397
|View full text |Cite
|
Sign up to set email alerts
|

Punctuating the equilibrium: an application of policy theory to COVID-19

Abstract: COVID-19 has taught us that, when inadequately addressed, preexisting policy problems (e.g. weak coordination of healthcare and gaps in income supports) exacerbate the cost of crises (including deaths) and make policy responses more difficult. On a more hopeful note, the pandemic has also revealed that policymakers and bureaucrats, reputed as defenders of the status quo and glacially paced, are capable of moving nimbly when seized with necessity. This manuscript draws on Baumgartner and Jones' punctuated-equil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…Naturally, COVID-19 has afforded lessons in policy development, including ensuring policy solutions are strategic and forward-thinking, as opposed to short-sighted solutions, and the need to focus on equity, effectiveness, and efficiency, where relevant [ 18 ]. Attention should be paid to moving the health system from one of responding to the crisis at-hand to being more proactive and planning upstream, leaving no ne behind.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Naturally, COVID-19 has afforded lessons in policy development, including ensuring policy solutions are strategic and forward-thinking, as opposed to short-sighted solutions, and the need to focus on equity, effectiveness, and efficiency, where relevant [ 18 ]. Attention should be paid to moving the health system from one of responding to the crisis at-hand to being more proactive and planning upstream, leaving no ne behind.…”
Section: Discussionmentioning
confidence: 99%
“…Attention should be paid to moving the health system from one of responding to the crisis at-hand to being more proactive and planning upstream, leaving no ne behind. “Pre-existing policy problems not adequately addressed exacerbate the cost of crises (including deaths) and make policy responses more difficult” [ 18 ]. While discussed more broadly (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Until the COVID-19 pandemic struck Ireland, the media had a more ambivalent attitude to doctors than to nurses, who are invariably portrayed as frontline heroes. Now may be the opportunity to reframe media and public perceptions of the medical profession, changing the 'policy image, ' which Baumgartner and Jones, as reported by Amri and Drummond, 26 define as "how public policies are discussed in public and in the media. " The radical health systems and workforce changes that are required go far beyond renegotiating the terms and conditions of consultants' contracts.…”
Section: Covid-19 -Impact and Opportunitymentioning
confidence: 99%
“…Policy equilibrium was punctuated by rapidly changing demands. Amri and Drummond (2020) found that in such circumstances, "policy-makers and bureaucrats, reputed as defenders of the status quo and glacially paced, are capable of moving nimbly when seized with necessity" (p. 33). Jones's (1991, 2010) punctuated equilibrium theory accommodates such demands.…”
Section: Introductionmentioning
confidence: 99%
“…True et al (2019) suggest that such policy punctuations "spring from either a change in preferences or a change in attentiveness" (p. 163). Punctuated equilibrium theory has been used to gain insights into shifts arising from the COVID-19 pandemic in health policy (Amri and Drummond, 2020), environment policy (Garfinkel, 2021) and quarantine policy (Moloney and Moloney, 2020).…”
Section: Introductionmentioning
confidence: 99%